Factores que limitan la conservación y promoción de los recursos y/o atractivos turísticos del distrito de Chazuta provincia de San Martín - Altamirano Altamirano, Marina (2007)
The tourism has turned into a fundamental sector of the economic activity from the last part of the 20th century, and everything indicates that it will continue growing in the next years. With this growth there is taking produced a diversification of the products and tourist destinations and as consequence the demand such of tourism is increased also as: nature, ecotourism, visits to national and natural parks, rural tourism. The tourists nowadays are increasingly demanding in the different types of tourist services; accommodations, restoration, transport, recreation, guided, including the complementary services, all that with the aim to turn their trip into a significant and unforgettable experience. Likewise one started recognizing the importance of the resources and tourist natural and cultural attractions that possesses Chazuta's District, and the use adapting that would have for the future generations; from the tourist needs, to be in touch with the nature and its manifestations, the culture and its representations, and the combination of both they form the tourist activity in the free time and leisure since they are: the adventure, the hunt, the fishing, the photography, the scientific study established in promoting the human ethics on the nature, educating and become aware to the tourist of the natural processes and social organizations for its survival. Therefore the ecotourism is a modality of tourism orientated towards areas with natural and cultural exceptional values (including protected areas), that on the base of the activities recreational and educational that its promotes, its contributes to the local conservation, propitiates the direct and charitable participation of the local populations and all it holds to the involved ones to take the necessary precautions to minimize both ecological and cultural impacts. In this investigation the ecotourism is considered to be a point important to stimulate the Tourist Sustainable Development for example is a productive alternative not extractive that is coherent with the in force conceptions on the sustainable development, improving the quality of human life without exceeding the capacity of load of the ecosystems that sustain her since it tries to support the natural life and the cultural environment across the controlled trips, organized, planned and administered, using parameters of protection and conservation of the environment.